Flat plate two-phase heat spreader on the thermal management of high-power electronics: a review - Lim, Hyunmuk; Lee, Jungho (Journal of Mechanical Science and Technology, 2021)
As the cooling capacity of the active cooling devices has reached their allowable heat flux limit, heat spreading technologies are becoming more remarkable in the thermal management of high-power electronics. Flat plate two-phase heat spreaders (FTHSs) are advantageous for the thermal management of electronic devices due to their simplicity, power-free operation, and high reliability. This review is based on understanding the working mechanism and limitations of FTHSs. As the power density of electronic devices increases, researchers focus on performance improvement to overcome their malfunctioned working conditions. This review summarizes the major parameters of FTHS that affect heat transfer performance. Moreover, recent advances in FTHSs suggest that new design concepts can extend the maximum operating heat flux of thermal management devices. This review can establish a direction for studying higher-performance heat spreaders and identifying the latest trends.
Keywords: Cooling Capacity; Flat plate; Flat plate two-phase heat spreader; Ground planes; High power electronics; Performance; Thermal; Thermal ground plane; Two-phase heat spreader; Vapor chamber; Flat plate two-phase heat spreader; Heat pipe; Thermal ground plane; Thermal management; Vapor chamber